Hybrid graphene/silicon Schottky photodiode with intrinsic gating effect. (19th April 2017) - Di Bartolomeo, Antonio; Luongo, Giuseppe; Giubileo, Filippo; Funicello, Nicola; Niu, Gang; Schroeder, Thomas; Lisker, Marco; Lupina, Grzegorz
Abstract: We propose a hybrid device consisting of a graphene/silicon (Gr/Si) Schottky diode in parallel with a Gr/SiO2 /Si capacitor for high-performance photodetection. The device, fabricated by transfer of commercial graphene on low-doped n-type Si substrate, achieves a photoresponse as high as 3     A   W − 1 and a normalized detectivity higher than 3.5 × 10 12   cm   Hz 1 / 2     W − 1   in the visible range. It exhibits a photocurrent exceeding the forward current because photo-generated minority carriers, accumulated at Si/SiO2 interface of the Gr/SiO2 /Si capacitor, diffuse to the Gr/Si junction. We show that the same mechanism, when due to thermally generated carriers, although usually neglected or disregarded, causes the increased leakage often measured in Gr/Si heterojunctions. We perform extensive I – V and C - V characterization at different temperatures and we measure a zero-bias Schottky barrier height of 0.52 eV at room temperature, as well as an effective Richardson constant A **   =   4 × 10 − 5   A   cm − 2     K − 2 and an ideality factor n ≈ 3.6, explained by a thin (<1 nm) oxide layer at the Gr/Si interface.